2018
DOI: 10.1111/epp.12468
|View full text |Cite
|
Sign up to set email alerts
|

First record of Xylotrechus chinensis (Coleoptera, Cerambycidae) in Greece and in the EPPO region

Abstract: Xylotrechus chinensis belongs to the entomofauna of China, Japan, the Korean Peninsula and Taiwan. Prior to this paper it has been intercepted twice outside its native range, once in Philadelphia (USA) and once in Germany (Europe). In spring 2017, it was detected for the first time in Greece, in Heraklion city (Island of Crete) infesting the trunk of trees of Morus species planted near the harbour of the city. It can thus be hypothesized that X. chinensis was transported from its native range with commodities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 9 publications
(11 reference statements)
1
22
0
Order By: Relevance
“…The device attached to a mulberry listening for the cerambycid pest Xylotrechus chinensis. The signal Back in 2017, in the island of Crete, Greece, and in Spain, it was observed [25][26] that several mulberries appeared to bear exit tunnels (see Fig. 3-left) that had not been observed before.…”
Section: The Devicementioning
confidence: 84%
“…The device attached to a mulberry listening for the cerambycid pest Xylotrechus chinensis. The signal Back in 2017, in the island of Crete, Greece, and in Spain, it was observed [25][26] that several mulberries appeared to bear exit tunnels (see Fig. 3-left) that had not been observed before.…”
Section: The Devicementioning
confidence: 84%
“…Indeed, very shortly after, it was reported that in spring-summer 2017, around 200 mulberry trees near the harbour of the city of Heraklion (island of Crete, Greece) were found to be infested by this beetle. It was most likely introduced to the Heraklion area in 2014 or 2015 with commodities arrived at this port from its area of origin [ 6 ]. In July 2018, new outbreaks were detected in the Autonomous Community of València (Spain), specifically in Quartell and Sagunt (València) and Almenara (Castelló de la Plana) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Global trade and climate change facilitate the establishment of pest populations outside their native ranges. Larvae of invasive species breed in wooden pallets and are transported through ports, handling facilities or truck roads and, therefore, one after the other, species known to be ‘exotic pests’ appear in Europe [12] and US in places that are not biologically adapted to regulate their multiplication. Since identification of wood-boring larval insects is important for pest risk analysis and management, phytosanitary measures are commonly applied in points of entry such as commercial harbors and airports.…”
Section: Introductionmentioning
confidence: 99%